Renewable Syngas Production from Thermal Cracking of Glycerol over Praseodymium-Promoted Ni/Al2O3 Catalyst - Nor Shahirah, Mohd Nasir; Ayodele, Bamidele V.; Jolius, Gimbun; Lam, Su Shiung; Cheng, C. K. (Elsevier Ltd, 2016)
In this study, the kinetics of glycerol pyrolysis over a 3wt%Pr-20wt%Ni/77wt%α-Al2O3 catalyst was investigated. The catalyst was synthesized via wet-impregnation method and was characterized using temperature-programmed calcination (TPC), temperature-programmed reduction (TPR), N2-physisorption, FESEM imaging, X-ray diffraction and CO2-/NH3-temperature-programmed desorption (TPD). The catalytic activity of the as-synthesized 3wt% Pr-Ni/α-Al2O3 catalyst was evaluated in a stainless steel fixed bed reactor at temperatures that ranged from 973 K to 1073 K and a weight-hourly-space-velocity (WHSV) of 4.5×104 ml g-1 h-1 under the atmospheric condition. The main gaseous products from catalytic glycerol pyrolysis were H2, CO, CO2 and CH4 (descending ranking) with the highest H2 formation rate and H2 yield of 0.02593 mol g cat−1 s−1 and 29.04%, respectively. The analysis of the kinetic data obtained from the glycerol pyrolysis showed activation energy of 37.36 kJ mol-1. Based on the mechanistic modeling, it can be deduced that the rate determining step of the glycerol pyrolysis was via a single site associative adsorption with molecular surface reaction as the rate-determining step.